Management optimizing of banking operations - Пласконь, Світлана Андріївна; Кармелюк, Ганна Іванівна; Сенів, Галина Василівна (Technology audit and production reserves, 2014)
The stochastic optimization model of active and passive transactions in the conditions of uncertainty and risk of bank functioning is given in the article. The objective function of this model is the receiving of maximum profit, and restrictions are used for modeling balance conditions to attract and use of cash resources. This was due to the lack of elucidation in both domestic and foreign literature of the tasks concerning optimization of administrative decisions of banks that function under uncertainty and the risk of predicted revenue from the attraction and use of funds. The study found that the economic-mathematical model of a bank will combine two approaches as a financial intermediary, which has over time to maximize its value, and as a regulated organization that ensures reliable operation of the financial and credit system. Therefore, opportunities are presented to optimize control process of deposit and lending policies of banks using economic-mathematical modeling of banking operations, taking into account the stochastic conditions of bank functioning. These data are useful and important for the optimization of the active and passive banking operations in order to maximize the bank profits from the given operations.